Nanomaterials as electrocatalyst for hydrogen and oxygen evolution reaction: Exploitation of challenges and current progressions. (1st January 2021) - Paul, Shujit Chandra; Dey, Shaikat Chandra; Molla, Md. Ashraful Islam; Islam, Md. Shafiul; Debnath, Sotan; Miah, Muhammed Yusuf; Ashaduzzaman, Md.; Sarker, Mithun
Graphical abstract: Nanomaterials are being widely considered as electrocatalyst for the production of hydrogen nowadays. Due to their outstanding catalytic performance, research activities are ongoing to explore the efficient electrocatalyst. This review article will be focused on recent challenges and progression in developing the metal and metal-free electrocatalyst for HER/OER activity. Highlights: Mechanisms of HER and OER reaction in both acidic and alkaline medium were discussed. Multi-metallic alloy, oxides and hydroxides are promising electrocatalyst for HER/OER. Nanomaterials having amorphous structure possess better catalytic efficiency. Transitional metal doped MOFs are found to be more promising for HER activity. Abstract: Electrocatalytic water splitting is considered being an optimistic process and can be a sustainable source of renewable energy for the future. Although, the primary overpotential requirement and stability problem of the electrocatalysts make the process difficult for industrial applications, a cost-effective electrocatalyst with high surface area, stability, and bifunctional activity can eliminate such barriers in the upcoming eons. To date, metal alloys, metal hydroxides, metal oxides, metal derivatives (phosphides, sulfides, selenides, and carbides) metal–organic frameworks, hybrid and metal-free materials based electrocatalysts have been already developed for the overall water splitting. Herein, the challenges to enhance the activity, stability and durability in the metal (both noble metal and transitional metal) and metal-free based electrocatalyst for both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) are summarized. A general overview of the water splitting mechanism followed by various electrocatalyst are discussed mainly. Moreover, it is expected to provide a comprehensive summary and outlook at the end.